Copper oxide-carbon catalysts for the oxidation of methylene blue - Makamu, Anza Reliance (Vaal University of Technology, 2020)
Organic water pollutants such as dyes are difficult to biodegrade. In this study Fenton, photo-Fenton and photocatalysis were used to degrade methylene blue dye in the presence of copper oxide catalysts. The copper oxide catalysts were prepared with a precipitation reduction method. The effect of different preparation parameters on the catalyst properties and catalytic activity were investigated. The reducing agents, ascorbic acid (ASC, C6H8O6), hydrazine (N2H4), sodium boron hydride (NaBH4) and glucose (C₆H₁₂O₆) could be used to obtain the desired Cu2O phase. ASC, N2H4 and NaBH4 were able to reduce copper (II) to copper (I) at room temperature whereas glucose required a higher reduction temperature. Stoichiometric amounts of the reducing agents ASC, N2H4 and glucose and double the stoichiometric amount of NaBH4 were required to obtain Cu2O. A further increase in the amounts of NaBH4 and N2H4 resulted in the formation of copper metal (Cu (0)). High amounts of ASC did not over-reduce the copper. ASC also functioned as capping molecule and anti-oxidant preventing the oxidation of the Cu2O to CuO in air after preparation. Hydrazine was thus not able to protect the Cu2O against oxidation. The SEM results showed that an increase in the amount of the precipitating agent, NaOH, resulted in an increase in the particle sizes. The particle shapes changed from spherical to cubic when a high amount of NaOH was used with hydrazine as reducing agent. Smaller particle sizes were obtained when CuCl2 was used instead of CuSO4 and Cu(NO3)2. Larger crystallites formed when the preparation temperature was increased from room temperature to 100°C with glucose as reducing agent. TEM and XRD analyses showed that the micro-particles seen in SEM analyses are made up of nano-particles. The catalysts were not active for photocatalysis which may be explained by the oxidation of these nano-particles to form the photocatalytic inactive CuO. The catalysts were shown to be active for Fenton and photo-Fenton degradation. The addition of graphene and activated carbon to the Cu2O catalysts were detrimental to the catalytic activity. The percentage degradation of methylene blue by the Fenton reaction increased with an increase in the BET surface area from 1.5 m2/g to 10 m2/g and a further increase in the surface area resulted in a decrease in the percentage degradation. A direct correlation between the Fenton catalytic activity and the pore size were found which indicate that the reaction was mass transfer limited.
M. Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Methylene blue; Fenton degradation; Photo-Fenton degradation; Photodegradation; ASC; N2H4; NaBH4; Glucose; Catalytic activity; Dissertations, Academic -- South Africa.; Nanostructured materials.; Copper -- Oxidation.; Copper catalysts.